Low-carbon optimization operation of integrated energy system considering comprehensive demand response under improved carbon trading mechanism - Li, Jing; Gao, Xiying; Guo, Dan; Xia, Jingyi; Jia, Zhuting; Wang, Yue (Frontiers in Energy Research, 2024)
The integrated energy system considering comprehensive demand response can realize cascade utilization of energy and reduce carbon emissions. However, few studies explore the operation of IES considering the coupling markets of electricity and carbon trading. Based on the characteristics and specific needs of the integrated energy system, this paper establishes the mathematical model of each energy supply equipment, and studies the optimal energy supply method of the system. First, demand response is categorized into price and substitution types based on load response characteristics. Second, the price demand response models are established utilizing the price elasticity matrix, and substitution demand response models are developed considering the mutual conversion of electric and heat energy on the user-side. Subsequently, a baseline method is employed to allocate carbon emission quotas to the system without charge with considering the actual carbon emissions from gas turbines and gas boilers. This results in the formulation of an improved carbon trading mechanism tailored for integrated energy system. Finally, a low-carbon optimization operational model for integrated energy system is constructed with the multi-objective functions. The results of numerical case studies are presented to validate the performance of the proposed control method.